Design and CFD Simulation of Knockout Drum - Ali, Yazen Munaf; Saleh, Dr Saad Nahi; Ayash, Wameed Abdulhassan; Ghani, Saramd Zaki; Salih, Sudad Adil (Journal of Petroleum Research and Studies, 2020)
Recently, the emission of black smoke over local area of Basra Oil Company from flare system represents a big problem facing the company and causing huge pollution in the surrounding environment. The main reason of emission black smoke is carryover of droplets of the rest hydrocarbons such as condensate and droplets of crude oil by gases which are came from degassing stations facility in the north Rumelia field, southern Iraq. In this study, a design methodology was developed for designing the knockout drum, and different design criteria were used in sizing and selecting the drum based on the specification of the inlet fluid mixture. Three designs of knockout drums with respect to the gas conditions were performed. The horizontal knockout drum with a diameter of 2.5 m and length of 5.5 m was simulated using a Computational Fluid Dynamics (CFD) model (ANSYS FLUENT 15.0). The CFD model predicted very well the two-phase flow behavior and proved the need for a vortex breaker at the liquid outlet. The CFD simulation revealed quantitatively that the design configuration of the knockout drum performed the separation of condensate droplets from natural gas with excellent efficiency.